Electrocardiographic Findings and Serum Troponin I in Carbon Monoxide Poisoned Patients - Scott Reza Jafarian Kerman; Nader Tavakkoli; Shokoufeh Hajsadeghi; Ali Shahabadi; Mojtaba Khojand (Acta Medica Iranica, 2012)
Carbon monoxide (CO) poisoning, though with different sources, is one of the most deadly emergencies in all countries. CO can threaten men's life by several paths especially cardiac complications, which can mimic other cardiac problems such as myocardial infarction. The objective of this study was to determine ECG findings and serum troponin I levels in CO poisoned patients. In this analytical cross-sectional study, 63 CO poisoning patients were consecutively included from hospital's emergency departments. CO content was measured by a CO-oximeter and an electrocardiography was taken first thing on admission. Arterial blood gas (ABG), troponin I and other data was collected afterwards. Data were divided by age groups (adults and children) and gender. CO content was significantly higher only in subjects with normal T wave compared to patients with inverted T wave in their initial ECG (P=0.016). No other significant difference was noticed. None of the ABG findings correlated significantly with CO content. Also no significant correlation was found with CO content after stratification by gender and age groups, but pH in children (r=-0.484, P=0.026). CO content was significantly higher in adults (P=0.023), but other ABG data were not significantly different. Only 3 patients had elevated troponin I. Receiver operating characteristic (ROC) analysis showed no significant cutoff points in CO content for ECG changes. No significant specific change in electrocardiograms (ECG) could contribute carboxyhemoglobin content in carbon monoxide poisoned patients. In addition, no specific difference was found between adults and pediatric subjects' ECGs. All other findings seemed to be accidental.